2022
DOI: 10.1055/s-0042-1757597
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental Knee Arthroplasty Has Lower Infection, Conversion, and Complication Rates Compared to High Tibial Osteotomy

Abstract: Introduction Isolated medial knee osteoarthritis can be surgically treated with either unicompartmental knee arthroplasty (UKA) or high tibial osteotomy (HTO). Proponents of UKA suggest superior survivorship, while HTO offers theoretically improved alignment and joint preservation delaying total knee arthroplasty (TKA). Therefore, we compared complications in a large population of patients undergoing UKAs or HTOs. We specifically assessed 90 days, 1 year, and 2 years: (1) periprosthetic joint infection (PJI) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Although high tibial osteotomy (HTO) also holds a place in the treatment of knee OA with non-TKA, clinical reports suggest that UKA has better clinical efficacy and lower incidence of complications compared with HTO. 20 , 21 The results of this study also revealed that the KSS improved significantly following UKA from an average preoperative score of 64.2 points to 89.7 points postoperatively. According to previous clinical follow-up studies, the ten-year UKA survival rate was between 80.6% and 84.0%.…”
Section: Discussionsupporting
confidence: 60%
“…Although high tibial osteotomy (HTO) also holds a place in the treatment of knee OA with non-TKA, clinical reports suggest that UKA has better clinical efficacy and lower incidence of complications compared with HTO. 20 , 21 The results of this study also revealed that the KSS improved significantly following UKA from an average preoperative score of 64.2 points to 89.7 points postoperatively. According to previous clinical follow-up studies, the ten-year UKA survival rate was between 80.6% and 84.0%.…”
Section: Discussionsupporting
confidence: 60%
“…The changes in indications and contraindications are listed in Table 1. Many studies have demonstrated that UKA is associated with certain advantages, such as shorter stays in the hospital, fewer complications, better postoperative function and quicker recovery 8,9 . UKA includes two prosthesis bearing designs—fixed‐bearing (FB) and mobile‐bearing (MB)—both with certain advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that UKA is associated with certain advantages, such as shorter stays in the hospital, fewer complications, better postoperative function and quicker recovery. 8 , 9 UKA includes two prosthesis bearing designs—fixed‐bearing (FB) and mobile‐bearing (MB)—both with certain advantages and disadvantages. The FB is accepted by most surgeons due to its low dislocation rate and the simplicity of the procedure.…”
Section: Introductionmentioning
confidence: 99%